Volatile Organic Compounds Trapping from Gaseous Samples on the Basis of Co-Liquefaction with Organic Solvent for Gas Chromatographic Analysis - Djozan, Djavanshir; Jouyban, Abolghasem; Mohammadandashti, Parastou (Current Analytical Chemistry, 2017)
Background: Volatile organic compounds (VOCs) are emitted from a variety of industrial sources and human exhaled breath with endogenous and exogenous origins. For environmental, health, and scientific studies, these compounds must be monitored at trace levels in airborne, gaseous samples and human breath exhales. This article presents the challenges for developing a simple, rapid, non expensive and adsorbent free method for the isolation and enrichment of volatile organic compounds (VOCs) from gaseous samples on the basis of co-liquefaction of analytes and solvent molecules. Methods: A 500 mL spherical glass device was filled with an air sample or human breath exhaled. 0.5 mL of acetone was introduced and exposed to ultra sonification for cold vaporization and then cooled down at -10ºC for co-liquefaction of acetone accompanying with VOCs. Parameters affecting performance of the extraction method were investigated using a mixture of benzene, toluene, ethyl-benzene and xylenes (BTEX) as the model VOCs. For quantitative investigation, 2 μL of the extract was subject to GC-FID analysis. Results: Under optimal conditions, the method displayed good linearity for BTEX within a range of 0.3-800 ng mL-1, with correlation coefficients >0.996. The limits of detection (LODs) and the limits of quantitation (LOQs) ranged from 0.13 to 0.25 ng mL-1 and 0.3 to 0.85 ng mL-1, respectively. The relative standard deviations (n=3) were less than 4.53%. Moreover, enrichment factors (EFs) and extraction recoveries (ERs) were in the ranges of 1075 to 1296-fold and 86-103%, respectively. The overall time for sampling and extraction is 20 min. Conclusion: A novel enrichment method was provided for extraction of volatile analytes from gaseous samples prior to their gas chromatographic analysis. The method is applicable to analyze samples of environmental and/or toxicological interests.
Keywords: organic solvent